Favorable Biochemical Freedom From Recurrence With Stereotactic Body Radiation Therapy for Intermediate and High-Risk Prostate Cancer: A Single Institutional Experience With Long-Term Follow-Up - Ricco, Anthony; Barbera, Gabrielle; Lanciano, Rachelle; Feng, Jing; Hanlon, Alexandra; Lozano, Alicia; Good, Michael; Arrigo, Stephen; Lamond, John; Yang, Jun (Frontiers in Oncology, 2020)
Purpose/Objective(s): The current study reports long term overall survival (OS) and biochemical freedom from recurrence (BFFR) following stereotactic body radiation therapy (SBRT) for men with intermediate and high-risk prostate cancer in a single community hospital setting with early adoption. Materials/Methods: Ninety-seven consecutive men with intermediate and high-risk prostate cancer treated with SBRT between 2007-2015 were retrospectively studied. Categorical variables for analysis included National Comprehensive Cancer Network (NCCN) risk group, race, Gleason grade group (GGG), T stage, use of androgen deprivation therapy (ADT) and Planning Target Volume (PTV) dose. Continuous variables for analysis included pretreatment prostate specific antigen (PSA), percent cores positive, age at diagnosis, PSA nadir, prostate volume, percent prostate that received 40Gy, and minimum dose to 0.03cc of prostate (Dmin). BFFR was assessed using the Phoenix nadir +2 definition. OS and BFFR were estimated using Kaplan-Meier (KM) methodology with comparisons accomplished using log-rank statistics. Multivariable analysis (MVA) was accomplished with a backwards selection Cox proportional hazards model with statistical significance taken at the p<0.05 level. Results: Median FU is 78.4 mos. Five and ten-year OS KM estimates are 90.9% and 73.2%, respectively, with 19 deaths recorded. MVA reveals pretreatment PSA (p=0.032), percent prostate 40Gy (p=0.003), and race (p=0.031) were predictive of OS. Five and nine-year BFFR KM estimates are 92.1% and 87.5%, respectively, with 10 biochemical failures recorded. MVA revealed PSA nadir (p<0.001) was the only factor predictive of BFFR. Specifically, for every one unit increase in PSA nadir, there was a 4.2-fold increased odds of biochemical failure (HR=4.248). No significant differences in BFFR were found between favorable intermediate, unfavorable intermediate, and high-risk prostate cancer (p=0.054) with 7-year KM estimates of 96.6%, 81.0%, and 85.7%, respectively. Conclusions: Favorable OS and BFFR can be expected following SBRT for intermediate and high-risk prostate cancer with non-significant differences seen for BFFR between favorable intermediate, unfavorable intermediate, and high-risk groups. Our 5-year BFFR compares favorably to the HYPO-RT-PC trial of 84%. PSA nadir was predictive of biochemical failure. This study is ultimately limited by the small absolute number of high- risk patients included.